Pelaksanaan Program Pendaftaran Tanah Sistematis Lengkap (PTSL) Di Desa Sukorejo Kecamatan Tunjungan Kabupaten Blora - Denyndra Arga R W B K; Edy Pranoto (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2023)
Complete Systematic Land Registration (PTSL) is a Land Registration activity for the first time which is carried out simultaneously for all Land Registration objects throughout the territory of the Republic of Indonesia in one village/kelurahan area. The purpose of this study was to determine the implementation of the Complete Systematic Land Registration (PTSL) program in Sukorejo, Tunjungan District and to find out the factors that became obstacles in the implementation of the Complete Systematic Land Registration (PTSL) program. The method in this research is a juridical method. The normative juridical method is based on the main legal materials to conduct research on relevant theories, concepts, legal principles and laws and regulations. The specification in this research is descriptive analysis. Sources of data used in this study are primary data and secondary data. The results of this study The implementation of the Complete Systematic Land Registration (PTSL) program has been going well in terms of standards and targets. PTSL officers have followed the instructions in accordance with Standard Operating Procedures (SOP) and have been understood by the parties involved in the implementation of the Complete Systematic Land Registration (PTSL) program in Tunjungan District, Blora Regency. Factors that become obstacles in the implementation of the Complete Systematic Land Registration (PTSL) program at the Blora District Land Office are internal factors.